El Cerro de la Ermita de La Encarnación (Caravaca de la Cruz, Murcia): santuario y territorio en el mundo ibérico del Sureste peninsular / The Cerro de la Ermita of La Encarnación (Caravaca de la Cruz, Murcia): cult place and territory in the Iron Age Iberian Southeast - Leticia López-Modejar (Panta rei, 2017)
As part of the landscape cult places developed an essential territorial role in the Mediterranean Protohistoric societies, including the Iberian communities. This role has not received the wide attention that it deserves in the Iberian Southeast, and particularly in the case study of the important sanctuary located in La Encarnación (Caravaca, Murcia). The aim of this paper is to insert this cult place within its spatial context and to analyze its territorial role from three perspectives: in connection with the oppidum, in relation to the territory controlled by this centre and, finally, beyond the territorial area of the oppidum. -- Los lugares de culto, como elementos del paisaje, desarrollaron un papel fundamental a nivel territorial entre las comunidades protohistóricas mediterráneas, incluido el propio mundo ibérico. Dicho papel ha sido sin embargo escasamente estudiado en el ámbito del Sureste y, concretamente, en el caso del importante santuario localizado en La Encarnación (Caravaca, Murcia). El objetivo del presente trabajo es insertar dicho lugar de culto en su contexto espacial, analizando su papel territorial desde una triple perspectiva: en conexión con el oppidum, en relación con el territorio vinculado a éste y, finalmente, su papel más allá del territorio de dicho oppidum.